Profiling Humans from their Voice - Singh, Rita (Springer Nature Singapore : Imprint: Springer, 2019)
This book is about recent research in the area of profiling humans from their voice, which seeks to deduce and describe the speaker's entire persona and their surroundings from voice alone. It covers several key aspects of this technology, describing how the human voice is unique in its ability to both capture and influence the human persona -- how, in some ways, voice is more potent and valuable then DNA and fingerprints as a metric, since it not only carries information about the speaker, but also about their current state and their surroundings at the time of speaking. It provides a comprehensive review of advances made in multiple scientific fields that now contribute to its foundations. It describes how artificial intelligence enables mechanisms of discovery that were not possible before in this context, driving the field forward in unprecedented ways. It also touches upon related and relevant challenges posed by voice disguise and other mechanisms of voice manipulation. The book acts as a good resource for academic researchers, and for professional agencies in many areas such as law enforcement, healthcare, social services, entertainment etc.